Kinerja Salesperson dan Kecerdasan Salesperson : Faktor kunci dari Keunggulan bersaing berkelanjutan bagi UMKM - Adi Santoso; Naning Kristiyana; Wahna Widhianingrum (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
This study was conducted with the aim of analyzing the effect of Salesperson performance and Salesperson intelligence on the competitive advantage of sustainable Reog handicraft SMEs in East Java. In this study, we will examine the influence of Salesperson intelligence and Salesperson performance in increasing sustainable competitive advantage in Reog handicraft SMEs. This study uses SMEs Reog Crafts in East Java as the research sample. This study uses multiple linear regression analysis on the first substructure and uses simple linear regression analysis on the second substructure. The results of this study found that Innate intelligence, Technology Intelligence, and Emotional Intellectual have a positive and significant influence on Salesperson Performance. In the second substructure test, it was found that Salesperson Performance had a positive and significant effect on SMEs Sustainable Competitive Advantage.